Akomodasi Komunikasi dalam Komunikasi Antarbudaya Santri Jawa di Pondok Pesantren Al Hikam Assalafiyyah, Bantarkawung - Reza Abineri; Fany Anggun Abadi; Viky Rizki Imanullah; Dede Suryadi (MUKASI: Jurnal Ilmu Komunikasi, 2025)
At Al Hikam Assalafiyyah Islamic Boarding School, Bantarkawung intercultural communication occurs almost daily. Ethnic differences among students bring variations to their communication behavior. For example, Javanese and Sundanese students enrich their interactions with their respective cultural quirks, which can sometimes lead to problems and even arguments. For example, when two individuals from Java and Sunda discuss papaya, the Javanese call it "gandul," while the Sundanese call it "gedang," where "gedang" in Javanese means banana. These differences in terms sometimes lead to arguments and fights between the two, resulting in conflict. This study focuses on intercultural communication at Al Hikam Assalafiyyah Islamic Boarding School, Bantarkawung. The theory used in this research is the Communication Accommodation Theory proposed by Howard Giles (2016). This theory emphasizes that adaptation is at the heart of communication, where individuals attempt to regulate or adjust their communication with others. This theory premise is that when interacting, people adjust their speech style, vocal patterns, and behavior to align with those of their interlocutors. Based on the explanation that has been explained above, the researcher is interested in conducting research on how Javanese students adapt with the title "Intercultural Communication Accommodation in the Self-Adjustment of Students at the Al Hikam Assalaffiyah Bantarkawung Islamic Boarding School, Brebes Regency".